Testing and Being Tested in Pandemic Times - Stark, David (Journal of Economic Sociology, 2020)
The coronavirus pandemic is witness to a great proliferation of two types of tests. The first type is testing —– new medical diagnostic tests as well as epidemiological models that simulate and project the course of the virus. In the second type, actors, organizations, and institutions are being tested in this moment of social and political crisis. This essay analyzes the similarities and differences between these two major types of tests in order to understand their entanglements in the crisis. In the process, we find a great diversity of tests operating in multiple registers, themselves not clearly demarcated, often combining and sometimes conflating, for example, scientific and public discourse. The study opens by identifying three aspects of testing, drawn from the sociology of testing. First, tests are frequently proxies (or projections) that stand for something. Second, a test is a critical moment that stands out – whether because it is a moment deliberately separated out or because it is a puzzling or troublesome “situation” that disrupts the flow of social life. Third, when someone or something is put to the test, of interest is whether it stands up to the challenge. These insights serve as the building blocks for addressing three major issues – representation, selection, and accountability – regarding testing in the time of the coronavirus crisis. In this moment we see a new model of testing: from statistical calculation of risk in a population to algorithmic prediction about the riskiness of particular persons.